2017
DOI: 10.2147/copd.s126970
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation with intelligent volume-assured pressure support versus pressure-controlled ventilation: effects on the respiratory event rate and sleep quality in COPD with chronic hypercapnia

Abstract: BackgroundCOPD patients who develop chronic hypercapnic respiratory failure have a poor prognosis. Treatment of choice, especially the best form of ventilation, is not well known.ObjectivesThis study compared the effects of pressure-controlled (spontaneous timed [ST]) non-invasive ventilation (NIV) and NIV with intelligent volume-assured pressure support (IVAPS) in chronic hypercapnic COPD patients regarding the effects on alveolar ventilation, adverse patient/ventilator interactions and sleep quality.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 29 publications
1
35
0
1
Order By: Relevance
“…The 2019 update resulted in eight RCTs that met the inclusion criteria. 2,6,[9][10][11][12][13][14] The details of the search and exclusion criteria are displayed in the flow diagram ( Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…The 2019 update resulted in eight RCTs that met the inclusion criteria. 2,6,[9][10][11][12][13][14] The details of the search and exclusion criteria are displayed in the flow diagram ( Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…VAPS has already been examined for the treatment of chronic respiratory failure, OHS and NMD. [6][7][8][9][10][11] There is growing evidence that VAPS is as effective as manually titrated pressure support (PS) ventilation for treating respiratory insufficiency or failure. 6,10,[12][13][14][15] Some conditions that could be treated with VAPS may also have a component of upper airway obstruction; patients might therefore benefit from automatically adjusting EPAP (AutoEPAP).…”
Section: Summary At a Glancementioning
confidence: 99%
“…Advances in technology demonstrate that NIV devices could meet changes in ventilation demand by automatically adjusting inspiratory pressure via the volume‐assured pressure support (VAPS) algorithm. VAPS has already been examined for the treatment of chronic respiratory failure, OHS and NMD . There is growing evidence that VAPS is as effective as manually titrated pressure support (PS) ventilation for treating respiratory insufficiency or failure …”
Section: Introductionmentioning
confidence: 99%
“…Most studies around the use of Va‐BPAP have been conducted in patients with obesity hypoventilation syndrome or COPD presenting with chronic respiratory failure . However, Va‐BPAP has also been successfully used in congenital central hypoventilation syndrome and restrictive chest wall disorders .…”
Section: Volume‐assured Pressure Supportmentioning
confidence: 99%
“…Most studies around the use of Va-BPAP have been conducted in patients with obesity hypoventilation syndrome or COPD presenting with chronic respiratory failure. [52][53][54][55][56][57] However, Va-BPAP has also been successfully used in congenital central hypoventilation syndrome 58 and restrictive chest wall disorders. [59][60][61] Early studies reported better control of nocturnal CO 2 with volume assurance compared to fixed pressure BPAP, 53,57 although this was often achieved at the expense of poorer sleep quality.…”
Section: Clinical Studiesmentioning
confidence: 99%